Antibacterial potential of strawberries and basil extracts combination against Streptococcus sanguinis (ATCC 10556) - Dharsono, Hendra Dian Adhita; Nurdin, Denny; Fatriadi, Fajar; Gondowidjojo, Yolanda Dwiutami; Yunita, Ellizabeth; Apriyanti, Eti (Padjadjaran Journal of Dentistry, 2021)
Introduction: Streptococcus sanguinis is a commensal microorganism as well as a pioneer colony in forming dental plaque. Oral biofilm formation can be prevented by a mechanical cleaning procedure followed by the use of mouthwash. The current gold standard for mouthwash is chlorhexidine. Nevertheless, it has side effects that are not recommended for long-term use. Previous studies had proven that herbal-based mouthwashes such as basil leaves (Ocimum basilicum) and strawberry fruit (Fragaria x ananassa) have been shown to have antibacterial properties. The effectivity of antibacterial activity phenomenon in combined extracts has been reported in other studies. This research aims to observe the antibacterial potential of the F. x ananassa and O. basilicum extract combinations against S. sanguinis (ATCC 10556). Methods: The sample of this study was a combination of F. x ananassa and O. basilicum extract, which initially screened for their antibacterial activities. Antibacterial activities of F. x ananassa and O. basilicum extracts against S. sanguinis were observed using Kirby Bauer method, while Minimum Inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) by serial microdilution method. The 2% concentration from each extract was combined in 1:1, 1:2, and 2:1 volume ratio variations then tested for inhibitory zones, MIC, and MBC. Results: F. x ananassa extract had 0.125% and 0.25% for MIC and MBC respectively, while O. basilicum extract showed the value of MIC and MBC as 0.031% and 0.063% against S. sanguinis (ATCC 10556). The extract combinations in 1:1, 1:2, and 2:1 volume ratio variations showed 0.016% for MIC and 0.031% for MBC. Conclusions: It was concluded that combining extracts of 2 % F. x ananassa and 2% O. basilicum in various ratios were observably to have the antibacterial potential against S. sanguinis (ATCC 10556).